2019
DOI: 10.1002/wer.1157
|View full text |Cite
|
Sign up to set email alerts
|

Health effects associated with wastewater treatment, reuse, and disposal

Abstract: This paper highlights the review of scientific literature published in the year 2018 on issues related to health risks associated with human and the general environment on the reuse of wastewater, treatment as well as disposal. The literature review on the above issues divided into number of sections, and these sections include management of wastewater, wastewater reuse with focus on microbial hazards, and chemical hazards. Further, the review also provides some recent research related to wastewater treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…Existing scientific research on viruses in water and wastewater recycling processes has also produced substantial evidence of the routes of human infection by pathogens in water. 12 Because coronaviruses can remain infectious for days in sewage and for longer periods in drinking water, water contaminated by coronaviruses is a potential vehicle for human exposure if aerosols are generated. 5,8 For example, during the 2003 SARS outbreak, the aerosolization of water droplets containing coronaviruses from a leaking sewage pipe in a residential apartment resulted in a cluster of cases spread through a community in Hong Kong.…”
Section: Is Coronavirus Infectious If Present In Water?mentioning
confidence: 99%
“…Existing scientific research on viruses in water and wastewater recycling processes has also produced substantial evidence of the routes of human infection by pathogens in water. 12 Because coronaviruses can remain infectious for days in sewage and for longer periods in drinking water, water contaminated by coronaviruses is a potential vehicle for human exposure if aerosols are generated. 5,8 For example, during the 2003 SARS outbreak, the aerosolization of water droplets containing coronaviruses from a leaking sewage pipe in a residential apartment resulted in a cluster of cases spread through a community in Hong Kong.…”
Section: Is Coronavirus Infectious If Present In Water?mentioning
confidence: 99%
“…It is therefore a point of call to know the longevity of the virus once discharged into wastewater to preserve aquatic ecosystems (Leung et al 2003). Based on the SARS-CoV pandemic in 2003, it was reported that the virus can survive and multiply within a short period if disinfection is not done and can be contagious (Wigginton et al 2015;Choudri and Charabi, 2019).…”
Section: Coronavirus and Wastewatermentioning
confidence: 99%
“…Scientific researchers have reported the possibility of human infection of viruses from water and wastewaters (Choudri and Charabi, 2019). The virus can remain active for days in sewage and it can be transmitted from wastewater to humans if aerosols are generated (Hung, 2003;Casanova et al 2009).…”
Section: Case Studies On the Presence Of Coronavirus In Wastewatermentioning
confidence: 99%
“…Multiple studies examined the potential health impacts and risk assessment associated with sludge and biosolids. Choudri and Charabi (2019) present a review of the literature related to health risks associated with the reuse of wastewater, including sludge and biosolids. Nkinahamira et al (2019) presented risk in terms of mobility and retention time of a suite of 48 elements in land application conditions with Ni, Cu, Zn, Cd, Cr, Co, Sr, Ca, Mn, Mo, Re, and W having the highest mobility and lowest retention times.…”
Section: Life Cycle and Risk Assessmentsmentioning
confidence: 99%